A load balanced approach of multicast routing and wavelength assignment in WDM networks. (2015) - Barat, Subhendu; Pal, Ajit; De, Tanmay
Multicast routing and wavelength assignment (MRWA) deals with the problem of one-to-many communication in a wavelength division multiplexed optical fibre networks. As physical optical networks are equipped with finite number of optical channels in each fibre cable, throughput of the network is treated as a major performance issue. The aim of this work is to maximise throughput in a finite wavelength WDM network. As to establish multicast session a single message may need to split into multiple messages fanning out of a node, the node must contain costly splitters. This work also considers the cost of splitting at the split nodes while establishing a light-tree for a particular multicast session request. Here a load-balancing technique is used to optimise the optical channel requirements to establish a multicast connection. The algorithm proposed here is compared with standard all-shortest path algorithm combined with first-fit wavelength assignment for multicasting by simulation on various network topologies and different network configurations. The simulation result shows that our proposed algorithm performs much better than the standard one.